PENGARUH KOMPENSASI FINANSIAL, PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA BAKUNG SARI HOTEL KUTA, BADUNG - Handika, Putu Yogi; Salit Ketut Netra, I Gst. (E-Jurnal Manajemen; Vol 5 No 5 (2016), 2016)
Hotel is one of the service industries that provide accommodation or lodging. Competition is becoming increasingly fierce with the emergence of various kinds of hospitality industries such as villas, resort, apartment and bungalow. Basic scientific papers proving the influence of financial compensation as well as education and training determine the effect of positive and significant impact on the performance of employees at Bakung Sari Hotel. Scientific papers choose a location in Bakung Sari Hotel with testing data analysis techniques aided linear regression. Using census methods (total sampling) the number of samples obtained as many as 53 respondents. Results of data with SPSS program proves it can be concluded that the financial compensation, education and training simultaneously significant effect on the performance of employees with R2 values of 84.0 percent. While the remaining 16.0 percent is influenced by other variables. financial compensation, education and training of positive and significant impact on the performance of employees partially. This can be evidenced from t value greater than t table (1.671) .
Keywords: Performance, financial compensation, Education and Training